Selection footprints reflect genomic changes associated with breeding efforts in 56 cucumber inbred lines. Issue 1 (15th November 2019) - Liu, Bin; Guan, Dailu; Zhai, Xuling; Yang, Sen; Xue, Shudan; Chen, Shuying; Huang, Jing; Ren, Huazhong; Liu, Xingwang
Abstract: Cucumber selective breeding over recent decades has dramatically increased productivity and quality, but the genomic characterizations and changes associated with this breeding history remain unclear. Here, we analyzed the genome resequencing data of 56 artificially selected cucumber inbred lines that exhibit various phenotypes to detect trait-associated sequence variations that reflect breeding improvement. We found that the 56 cucumber lines could be assigned to group 1 and group 2, and the two groups formed a distinctive genetic structure due to the breeding history involving hybridization and selection. Differentially selected regions were identified between group 1 and group 2, with implications for genomic-selection breeding signatures. These regions included known quantitative trait loci or genes that were reported to be associated with agronomic traits. Our results advance knowledge of cucumber genomics, and the 56 selected inbred lines could be good germplasm resources for breeding.